2015
DOI: 10.1111/1750-3841.12795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Extraction Techniques, Solid‐Phase Microextraction Versus Continuous Liquid–Liquid Extraction/Solvent‐Assisted Flavor Evaporation, for the Analysis of Flavor Compounds in Gueuze Lambic Beer

Abstract: Lambic is a beer style that undergoes spontaneous fermentation and is traditionally produced in the Payottenland region of Belgium, a valley on the Senne River west of Brussels. This region appears to have the perfect combination of airborne microorganisms required for lambic's spontaneous fermentation. Gueuze lambic is a substyle of lambic that is made by mixing young (approximately 1 year) and old (approximately 2 to 3 years) lambics with subsequent bottle conditioning. We compared 2 extraction techniques, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…These findings align with results from a previous study where SAFE has been reported to be better suited for the extraction of acids and alcohols in beer [9]. As HSSE, SBSE, and HS-SPME use very similar mechanisms for the extraction of VOCs, the overall affinity of SPEs (HSSE, SBSE, and HS-SPME) for the extraction of esters was similar.…”
Section: F I G U R E 4 Heat Map Of the Extraction Methods (Column) Fosupporting
confidence: 90%
See 1 more Smart Citation
“…These findings align with results from a previous study where SAFE has been reported to be better suited for the extraction of acids and alcohols in beer [9]. As HSSE, SBSE, and HS-SPME use very similar mechanisms for the extraction of VOCs, the overall affinity of SPEs (HSSE, SBSE, and HS-SPME) for the extraction of esters was similar.…”
Section: F I G U R E 4 Heat Map Of the Extraction Methods (Column) Fosupporting
confidence: 90%
“…Both techniques require the volatiles to be extracted before the analysis. The most common methods used to extract VOCs from beer and other alcoholic beverages are headspace solid‐phase microextraction (HS‐SPME) , headspace sampling (purge and trap, or static) , simultaneous distillation extraction (SDE), which combines distillation with liquid–liquid solvent extraction , or solvent‐assisted flavor evaporation (SAFE) . Relatively new methods gaining popularity are stir bar sorptive extraction (SBSE) and headspace sorptive extraction (HSSE) using Twister® .…”
Section: Introductionmentioning
confidence: 99%
“…The DVB/CAR/PDMS SPME fiber was reported by Rodriques et al [4] as able to provide more complete volatile profiles, due to the wider range of volatile and semi-volatile compounds detected. A study comparing SPME with continuous liquid-liquid extraction/solvent-assisted flavor evaporation (CLLE/SAFE) for lambic beer reported that SPME recovered more esters but CLLE/SAFE recovered a greater number of acid compounds [16]. Others have shown that SPME-GCMS is useful for analysing volatiles in a wide range of beer styles [17].…”
Section: Solid Phase Microextraction Analysis Of Volatilesmentioning
confidence: 99%
“…Meanwhile, as for the headspace options, the most widely utilized have been dynamic headspace sampling [5] and SPME [6]. Although the choice of the method depends on the type of food and the information being sought [7], among a variety of other factors, SAFE and SPME have frequently been used in a complementary manner in Article Related Abbreviations: AOAC, Association of Official Analytical Chemists; LM, lipases method; SAFE, solvent-assisted flavour evaporation order to obtain a complete profile of the overall flavor compounds [8][9][10][11][12]. SAFE extracts have reportedly been richer in high-molecular weight volatile compounds, while SPME extracts have been richer in low-molecular weight volatile compounds [13].…”
Section: Introductionmentioning
confidence: 99%